Determinación de las condiciones óptimas de operación del intercambiador de calor en cascada, de un sistema de refrigeración con propano y dióxido de carbono (2018)
In this document, a cascade cooling system is modeled and analyzed with propane C3H8 and carbon dioxide Co2. As a tool for the implementation of the model, the Python programming language, using the Spyder interpreter of the anaconda Suit. Initially The cascade cooling system and its components were characterized, afterwards the a balance of mass and energy, taking into account the variables of the environment to be controlled in the interior and exterior of the refrigeration cycle, in accordance with the general conditions of the tests for the equipment to be evaluated, establishing the operating ranges for the temperature (-50 ° C a - 10 ° C) in the CO2 stage, (-15 ° C a 30 ° C) in the C3H8 stage, the room temperature TH of 25 ° C and of the cold space TL of -45 ° C. With the approach of the mathematical model based on the first and second law of the thermodynamic behavior of the cascade cooling system was observed using C3H8 and Co2, a detailed analysis of the mass and energy balances of each team and a study of sensitivity to the CO2.